Precision Effects of Glibenclamide on MRI Endophenotypes in Clinically Relevant Murine Traumatic Brain Injury. Issue 2 (16th December 2022) - Zusman, Benjamin E.; Wu, Yijen; Kochanek, Patrick M.; Vagni, Vincent E.; Janesko-Feldman, Keri; Gerzanich, Volodymyr; Simard, J. Marc; Karahalios, Katherine; Mihaljevic, Sandra; Raikwar, Sudhanshu; Rani, Anupama; Rulney, Jarrod; et al.
Abstract : OBJECTIVES: Addressing traumatic brain injury (TBI) heterogeneity is increasingly recognized as essential for therapy translation given the long history of failed clinical trials. We evaluated differential effects of a promising treatment (glibenclamide) based on dose, TBI type (patient selection), and imaging endophenotype (outcome selection). Our goal to inform TBI precision medicine is contextually timely given ongoing phase 2/planned phase 3 trials of glibenclamide in brain contusion. DESIGN: Blinded randomized controlled preclinical trial of glibenclamide on MRI endophenotypes in two established severe TBI models: controlled cortical impact (CCI, isolated brain contusion) and CCI+hemorrhagic shock (HS, clinically common second insult). SETTING: Preclinical laboratory. SUBJECTS: Adult male C57BL/6J mice ( n = 54). INTERVENTIONS: Mice were randomized to naïve, CCI±HS with vehicle/low-dose (20 μg/kg)/high-dose glibenclamide (10 μg/mouse). Seven-day subcutaneous infusions (0.4 μg/hr) were continued. MEASUREMENTS AND MAIN RESULTS: Serial MRI (3 hr, 6 hr, 24 hr, and 7 d) measured hematoma and edema volumes, T2 relaxation (vasogenic edema), apparent diffusion coefficient (ADC, cellular/cytotoxic edema), and 7-day T1-post gadolinium values (blood-brain-barrier [BBB] integrity). Linear mixed models assessed temporal changes. Marked heterogeneity was observed between CCI versus CCI+HS in terms of different MRI edema endophenotypes generated (all p < 0.05). Glibenclamide had variable impact. High-dose glibenclamide reduced hematoma volume 60% after CCI (p = 0.0001) and 48% after CCI+HS (p = 4.1 × 10–6) versus vehicle. Antiedema benefits were primarily in CCI: high-dose glibenclamide normalized several MRI endophenotypes in ipsilateral cortex (all p < 0.05, hematoma volume, T2, ADC, and T1-post contrast). Acute effects (3 hr) were specific to hematoma (p = 0.001) and cytotoxic edema reduction (p = 0.0045). High-dose glibenclamide reduced hematoma volume after TBI with concomitant HS, but antiedema effects were not robust. Low-dose glibenclamide was not beneficial. CONCLUSIONS: High-dose glibenclamide benefitted hematoma volume, vasogenic edema, cytotoxic edema, and BBB integrity after isolated brain contusion. Hematoma and cytotoxic edema effects were acute; longer treatment windows may be possible for vasogenic edema. Our findings provide new insights to inform interpretation of ongoing trials as well as precision design (dose, sample size estimation, patient selection, outcome selection, and Bayesian analysis) of future TBI trials of glibenclamide.